The Impact of Discovery Learning with Interactive Fraction Board Media on Fourth-Grade Students' Mathematical Engagement - Firnanda, Nabila; Indianasari, Indianasari (Journal of Innovation and Research in Primary Education, 2025)
Elementary students frequently struggle with fraction concepts due to their abstract nature, resulting in passive learning behaviors and limited engagement. This study examined the effect of the Discovery Learning model assisted by interactive fraction board media on fourth-grade students' learning activity in fraction instruction. A pre-experimental design with One Group Pretest-Posttest configuration was employed at SD Negeri 01 Trans Bangsa Negara. Eleven fourth-grade students participated using saturated sampling technique. Learning activity was measured through structured observation sheets assessing participation, enthusiasm, interaction, and perseverance dimensions. The intervention implemented six-step Discovery Learning process combined with interactive fraction board media allowing physical manipulation of fraction representations. Data analysis utilized descriptive statistics to examine changes in learning activity scores between pretest and posttest conditions. Significant improvements in learning activity were observed following the intervention. Mean scores increased from 2.45 (pretest) to 4.18 (posttest), representing a 1.73-point improvement. The percentage of students in "less active" category decreased from 45.5% to 0%, while those achieving "active" or "very active" status increased from 9.1% to 81.8%. All students demonstrated enhanced engagement across measured dimensions. The findings support the effectiveness of combining Discovery Learning with interactive media for enhancing student engagement in fraction instruction. The intervention successfully addressed challenges associated with natural number bias and abstract fraction concepts through concrete manipulative experiences. Results align with Cognitive Load Theory and constructivist learning principles, demonstrating how interactive technologies can optimize learning environments and promote active participation in elementary mathematics education.